A bio-inspired semi-active vibration isolator with variable-stiffness dielectric elastomer: Design and modeling - Zhao, Yunhua; Meng, Guang (Journal of sound and vibration, 2020)
•A bio-inspired semi-active vibration isolator is proposed with dielectric elastomers used as the variable stiffness element.•An analytical model for the dielectric elastomer stiffness is developed and validated by the experimental data.•The parametric dependence of the dielectric elastomer stiffness is analyzed to provide guidance for a compact device with large range in stiffness This paper proposes a bio-inspired semi-active vibration isolator with the dielectric elastomer based variable stiffness element for the vibration suppression of the free-floating spacecraft. A theoretical model for the dielectric elastomer stiffness is developed and validated by the experimental data. The parametric dependence of the mechanical stiffness on the applied voltage, pre-stretch of the elastomer and dielectric material properties is analyzed. The approximate analytical solutions are obtained employing the harmonic balance method and confirmed by the numerical simulation of the original full governing equations. The root-mean-square values of the alternating components of the capture mechanism displacement and satellite platform displacement under the harmonic excitation (3 Hz) respectively decrease by 39.7% and 66.1% with the voltage of 4.0 kV. In the presence of the double-tone (3 Hz mixed with 7 Hz) external force, vibration attenuation of 40.5% and 66.4% in comparison with the responses at zero voltage, are achieved respectively for the capture mechanism and satellite platform. Compared to the classical linear-structure based vibration isolator, the presented bio-inspired isolator shows enhanced vibration isolation performance. The results demonstrate the effectiveness of the proposed system for adjustable stiffness based semi-active vibration control.